Pencegahan DHF (Dengue Haemorrhagic Fever) pada Anak - Sunarti; Padhila, Nur Ilah; Jama, Fatma; suhermi (Window of Community Dedication Journal, 2022)
Dengue Hemorrhagic Fever (DHF) is still an important health problem in Asia. Not only in Indonesia, in developed countries such as Japan and Singapore, DHF cases still catch the attention of the health authorities in each country. Dengue Hemorrhagic Fever in Indonesia is still a public health problem and is an endemic disease in almost all provinces. In the last 5 years, the number of cases and affected areas has continued to increase and spread widely. Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito. This disease attacks everyone and can cause death, especially in children, and often causes extraordinary events or epidemics throughout Indonesia. The partner problem found was the lack of knowledge of the patient's family regarding how to prevent Dengue Fever. The solution offered is in the form of health education on how to prevent dengue fever (DHF). The results of the implementation of the activities that have been carried out show that family knowledge has changed from not knowing to knowing where out of 12 families of patients who were given health education, there were 9 (75.0%) knowledgeable people and 3.0 (25%) parents who were knowledgeable. not enough. This is because 3 out of 12 of these people are elderly and do not really understand the Indonesian language used when the health counseling is being carried out, but most of the counseling participants understand and are enthusiastic about participating in the counseling until it is finished.